Hero - Grant, Michael, 1954- (Grant, Michael, 1954- Monster trilogy, 2020)
While the Rockborn Gang tries to outmaneuver a new supervillain created by meteorite shrapnel, Malik investigates the Dark Watchers and the possibility that their reality is advanced, elaborate simulation.